Geopolitical and Ideological Spaces of Eurasian Nation-Building - A. V. Renard-Koktysh (Сравнительная политика)
Russia’s case demonstrates that huge territory, the biggest number of neighbouring countries in the world, numerous ethnic groups and suffi cient reserves of natural resources have been historically used by elites to cultivate the idea of Russian state’s exclusiveness. Over the various epochs it has determined the authorities’ thinking style as an imperial one on the level of tacit knowledge, which has practically turned into extending the spheres of infl uence as well as into expansionism.